The Political Economy of Peace and Conflict - Azeez, Ismail Adaramola Abdul; Jimoh, Amidu Adinoyi (Green Publisher Indonesia, 2023)
This paper suggests that a ‘political economy’ approach to conflict has far-reaching implications for relief work. In war there are both ‘winners’ and ‘losers. The vulnerability of losers needs to be understood as a consequence of their powerlessness. A state of war provides and justifies the use of violent means to create or sustain economic profits and political power. A war may have clear ‘winners’ in the sense that they profit from the war without the war itself being ‘won’ in the traditional sense. For the losers, such a war is the never-ending accumulation of abuses, fear and frustration. The paper aims to find out how the political economy approach to conflict between peace and conflict. Descriptive method with qualitative approach was used in the study. The paper proposes that by understanding the political economy of war, relief agencies can better assess the, forms of economic violence which threaten livelihoods during wars. Second, analyzing the context and implications of relief work is crucial so as to minimize its negative impact – given that belligerents and foreign states may seek to manipulate a humanitarian presence and misdirect the resources provided by relief. Its further analysis methods of understanding the course of a conflict in terms of political economy can help to identify political and economic interests which impede a transition to peace, and so help avoid the reconstruction of a pre-war economy that may have had much to do with the origin of the conflict.